Analysis of mobile-oriented energy consumption for heterogeneous connections in hybrid wireless networks. (1st January 2012) - Abbas, Ziaul Haq; Li, Frank Y.
While more and more mobile devices are equipped with both cellular and WLAN interfaces for internet access, the energy consumption aspect of these connections has not been studied in depth in the literature. In this paper, a hybrid network with three alternative wireless connections, namely, a cellular component, a combined component with a mixed ad hoc and cellular link, or an infrastructure-based WLAN component, is investigated. A distance-based analysis on the energy consumption of a mobile station has been performed for each alternative wireless connection, and corresponding numerical results have been obtained. The results suggest that, to increase link throughput while maintaining minimal power consumption, the remaining energy of the mobile station as well as the amount of bytes communicated over a link should be taken into consideration for connection selection. Furthermore, the remaining battery level of the mobile station could also be used as the criterion for handover decision, from both the mobile station's and the network operator's perspectives.